Evaluation of Active Fire Protection Facilities at gas stations in Indragiri Hulu Regency - Wahyuni, Sri; Herniwanti, Herniwanti; Abidin, Aldiga Rienarti; Rahayu, Endang Purnawati; Zaman, M. Kamali (Budapest International Research and Critics University, 2021)
Fire is a threat to human safety, property and the environment. Fire incidents at gas stations often occur, at least from 2018-2020 there have been two fire cases in Indragiri Hulu Regency which resulted in physical and material losses. The fire occurred due to the unavailability and lack of monitoring of active fire protection facilities at gas stations. This type of research is a case study qualitative research which is determined by purposive sampling. The informants in this study consisted of 6 people, namely operators, field coordinators, technical staff, supervisors, leaders and directors of gas stations. The results obtained are that the gas station already has 2 fire detectors but does not meet the standard of SNI 03-3985-2000, Gas stations already have fire alarms but not yet installed in all buildings, gas stations already have 4 fire extinguishers and are not in accordance with Pertamina Regulation and PU Ministerial Regulation No. 26/PRT/M/2008, there is an absorbent in the form of sand with a blue tub and it is not in accordance with Pertamina standards, it already has a hydrant that meets the standard and already has hose reels. It is suggested to gas stations to increase the number of fire detectors, fire alarms, fire extinguishers, hydrants and absorbents in accordance with Pertamina standards.